Intron loss in interferon genes follows a distinct set of stages, and may confer an evolutionary advantage. (July 2016) - Krause, Christopher D.
Graphical abstract: Highlights: The promoter, ORF, 5′ UTR and 3′ UTR of IFN-λ genes are well conserved. Intronless IFN-λ cDNAs are not clustered with other IFN-λ genes. Intronless IFN-λ cDNAs almost always contain an intact promoter. Intronless IFN-λ genes are co-inserted with a highly duplicated genomic sequence elsewhere in the genome. IFN-λ gene evolution occurred repeatedly and independently in vertebrate lineages. Abstract: The promoter-intron-exon structure of genes evolve. While the structures of some IFN genes (e.g., piscine and amphibian Type I IFNs, most tetrapod IFN-λ genes) resemble those of other class II cytokines (e.g., interleukins-10, 19, 20, 22, 24, 26), the structures of other IFN genes differ significantly. Although all bony vertebrate IFN-γ genes lack the canonical third intron, and all amniote Type I IFN genes lack introns, only some IFN-λ genes lost their introns. Interestingly, these intronless IFN-λ genes are not preferentially related to one another nor are they clustered with canonical multi-intron IFN-λ genes. Hypothesizing that intronless IFN-λ genes repeatedly and independently evolved and transposed throughout the genome, we sought to understand the genetic processes involved in their intron loss and genomic migration. Utilizing the high conservation of the promoters, the UTRs and the ORFs of the IFN-λ genes, we collected data from two families of intronless IFN-λ genes, and developed a model supported by these data to explain how intronless IFN-λ genes evolved. (1) A cytoplasmic IFN-λ cDNA generated by reverse transcriptional activity enters the nucleus and attempts to recombine with its multi-exon progenitor. (2) Nuclear DNA synthesis at the 5′ and 3′ ends within recombination intermediates affixes the promoter onto the cDNA and preserves its 3′ UTR. (3) Resolution of the recombination complex releases the promoter-associated cDNA. (4) The released intronless gene co-integrates with a highly duplicated sequence undergoing transposition. We propose that this process explains not only the evolution of the gene structure of IFN genes, but also the increased transposition of intronless genes in genomes, and may confer an evolutionary advantage.